2008
DOI: 10.1055/s-2008-1081340
|View full text |Cite
|
Sign up to set email alerts
|

Thein vitroAnti-Osteoporotic Activity of some Diarylheptanoids and Lignans from the Rhizomes ofDioscorea spongiosa

Abstract: Three diarylheptanoids and three lignans from the 90 % ethanol fraction of the rhizomes of DIOSCOREA SPONGIOSA were isolated and subjected to IN VITRO experiments to investigate their activity on osteoblasts and osteoclasts. Diarylheptanoid 1 and furofuran lignan 6 were found to significantly stimulate the proliferation of primary osteoblasts and 6 also mildly stimulated osteoblast mineralization by mouse calvaria osteoblastic cells. All diarylheptanoids and lignans at a concentration of 200 muM completely inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Salicifoliol ( 9 ), magnone A ( 11 ), and planispine A ( 5 ), having no methylenedioxy groups, showed much less or no antifeedant activity. As it was reported, compounds with methylenedioxy groups have various bioactivities, such as improving skin condition, antioxidant activity [ 28 ], anti-inflammatory activity [ 29 ], radical scavenging activity [ 30 ], insecticidal activity [ 31 ], antineuroinflammatory effects [ 32 ], antiparasitic activity, and anti-osteoporotic activity [ 33 ]. Therefore, methylenedioxy, as an active chemical group, may play a key role in antifeedant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Salicifoliol ( 9 ), magnone A ( 11 ), and planispine A ( 5 ), having no methylenedioxy groups, showed much less or no antifeedant activity. As it was reported, compounds with methylenedioxy groups have various bioactivities, such as improving skin condition, antioxidant activity [ 28 ], anti-inflammatory activity [ 29 ], radical scavenging activity [ 30 ], insecticidal activity [ 31 ], antineuroinflammatory effects [ 32 ], antiparasitic activity, and anti-osteoporotic activity [ 33 ]. Therefore, methylenedioxy, as an active chemical group, may play a key role in antifeedant activities.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of dietary products with therapeutic effect on bone formation have been reported and several natural compounds have been shown to enhance osteogenic differentiation (9-13), such as red yeast rice (10), black cohosh (14), and green tea (13). The effect of yam extracts and their bioactive component on bone formation in vitro (5,9,15), in vivo (8,(16)(17)(18), and in human population samples (19) have been reported and so far all showed potential in the treatment of bone-related diseases, particularly in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have suggested the potential of several species of yam to inhibit bone resorption, as well as to promote bone formation. The phytochemicals from yam such as glycosides, lignans, diosgenin, and dioscin have all been reported to have anti-osteoporotic activity both in vitro and in vivo (5)(6)(7)(8). In our previous study, we reported that diosgenin, a major component of yam, showed osteogenic action through upregulating bone-specific transcription factor Runx2 and bone matrix protein synthesis in osteoblastic MC3T3-E1 cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 1,3- syn- diol moiety is largely found in compounds with biological properties, for example, various statins (drugs that lower cholesterol and reduce cardiovascular disease, fluvastatin, pitavastatin), 1,3,5,7- syn -tetrols are anticancer (cryptocaryols A and B), , antifungal (patricin A), , and antiosteoporotic (diospongin C) agents . Higher homologues (1,3,5,7,9 syn-pentols) also display antibiotic properties, as exemplified by blasticidin A, chainin, lagosin, and filipin III. , Efficient preparation of these important syn -polyols is highly challenging.…”
mentioning
confidence: 99%